Repair of Perineal Hernia Following Abdominoperineal Excision with Biological Mesh: A Systematic Review - Narang, Sunil K.; Alam, Nasra N.; Köckerling, Ferdinand; Daniels, Ian R.; Smart, Neil J. (Frontiers in Surgery, 2016)
Introduction Perineal hernia (PerH) following abdominoperineal excision (APE) procedure is a recognized complication. PerH was considered an infrequent complication of APE procedure; however, PerH rates of up to 45% have been reported in recent publications following a laparoscopic APE procedure. Various methods of repair of PerH with the use of synthetic meshes or myocutaneous flap have been described, although there is no general agreement on an optimal strategy. The use of biological meshes for different operations is growing in popularity, and these have been promoted as being superior and safer when compared to synthetic meshes. Although the use of biologics is becoming popular claims of better outcomes are largely unsupported by evidence. The aim of this systematic review is to evaluate the currently available evidence supporting the use of biologic or biosynthetic meshes for the repair of PerH that develop following an APE. Methods A systematic review of all English language literature relevant to repair of PerH following APE with biologic or biosynthetic mesh published between January 1, 2000 and July 31, 2016 was carried out using MEDLINE, EMBASE, and the Cochrane Library of Systematic Reviews for relevant literature. Searches were performed using a combination of Medical Subject Headings (MeSH) terms and text words “PerH,” “APE,” “morbidity,” “biologics,” “biosynthetic,” and “hernia.” Studies in which the use of biological meshes was not reported were excluded from the review. Various outcome measures, including operative technique, complication rates, recurrence rates, type of mesh, management of recurrences, and risk factors, were extracted. Oxford Centre for Evidence-based Medicine – Levels of Evidence (March 2009) was used to assess the quality of evidence. Results The systematic review of the literature identified three case reports, four case series, and one pooled analysis that were included in the final review. Overall, these studies were of poor quality providing level 4 evidence. Various different approaches and techniques of repair of PerH were described; however, it was difficult to extract information with regard to the primary and secondary outcome measures. Conclusion There is no general agreement to the optimal operative strategy to repair PerH following an APE. There is insufficient evidence to recommend any specific operative approach or repair technique for PerH following an APE.